Utility of Triglyceride-Glucose index in predicting glycemic control in type 2 diabetes mellitus - Timalsina, Santosh; Mahato, Shishir; Nepal, Sandesh (Birat Journal of Health Sciences, 2021)
Introduction: Insulin resistance (IR) and glycemic control are two very important aspects to be considered during management of patients with Type 2 Diabetes Mellitus (T2DM). The triglyceride-glucose (TyG) index has been proposed as a simple and inexpensive parameter that correlates well with IR and glycemic control.Objectives: To explore the association of TyG index (and other TyG derived indices) with glycated hemoglobin (HbA1c) and evaluate their predictive ability for glycemic control in patients with T2DM.Methodology: This cross-sectional study comprised of 160 adult patients diagnosed with T2DM visiting the medical outpatient department of Chitwan Medical College, Bharatpur, Chitwan between July–December 2019. Socio-demographic data and anthropometric measurements were collected. Glycemic control was assessed by HbA1c. TyG index was calculated by the formula: ln [fasting TG (mg/dl) x fasting glucose (mg/dl)/2]. Receiver operating characteristic (ROC) curve analysis was performed to analyze the predictive ability of TyG-index for poor glycemic control.Results: One hundred and sixty patients (mean age: 53.6 ± 10.7 years, 55.0% males) were included in the study. Eighty (50.0%) had good glycemic control (HbA1c